Effect of ssbA1 and lexC113 mutations on lambda prophage induction, bacteriophage growth, and cell survival. - Vales, L D (1980)
Escherichia coli strains containing mutations (ssbA1 and lexC113) which affect single-strand deoxyribonucleic acid binding protein have been examined. Among the properties studied were: sensitivity to ultraviolet irradiation and methyl methane sulfonate, temperature sensitivity, induction of prophage lambda by ultraviolet light, temperature, and mitomycin C, and deoxyribonucleic acid synthesis. Strains containing the ssbA1 and lexC113 mutations differ significantly in several of these properties.